KELAYAKAN HUMAN ELECTRIC BLOOD MEDIA PADA MATA PELAJARAN IPA SISTEM PEREDARAN DARAH MANUSIA FASE C PADA SISWA SEKOLAH DASAR - Fitriyani, Fitriyani (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This research aims to: 1) knowing how the natural sciences learning activities in Fase C. 2) Knowing the Media Development on natural sciences of the human blood circulatory system, 3) knowing the feasibility of Human Electric Blood Media on natural sciences of the human blood circulatory system in Fase C. The results showed that learning of natural sciences Fase C in the elementary school have been utilizing the media of instruction. The type of media Learning of natural sciences especially human blood circulatory system which have been used only media visual images this make the students difficult to understanding of the material and less enthusiastic when learning activities. Development of Human Electric Blood Media be an alternative in overcoming those problems. This type of research is development research, using the method of research and development (Research and Development / R & D). Media that have been developed validated by experts of natural sciences matter and instructional media expert. After repairs and validated by experts then carried out the assessment test product to the user, is students of Fase C as many as 16 students and 2 teachers. This research used data collection techniques of interview, observation, documentation, and questionnaire. Data analysis technique using quantitative and qualitative analysis. Research and development showed that produced the human electric blood media base LED. The results of the assessment of the eligibility level average media electric blood by 85% of incoming material in the category is very feasible, assessment of the media expert of 92% in the category of very decent, and the average user assessment by teachers and students amounted to 89.2% entered on categories is very decent.